Identification of High Herbage and Oil Yielding Variety (Jor Lab P-1) of Pogostemon cablin (Blanco) Benth Through Mutation Breeding. Issue 1 (2nd January 2018) - Lal, Mohan; Pandey, Sudin Kumar; Dutta, Sukriti; Munda, Sunita; Baruah, Joyashree; Paw, Manabi
Abstract: Pogostemon cablin (Blanco) Benth, also known as patchouli is an aromatic herb mainly used for high quality perfumery, aromatherapy and fragrances. The study was conducted to identify high yielding mutant genotype of patchouli through gamma radiation. In this experiment 14 different doses of gamma adiation were given to rooted slips of patchouli variety Johor. All 482 M2 progenies were produced and their morphological, qualitative and quantitative oil data were recorded. Advanced progenies were developed and finally selected a single plant from each M4 progenies on the basis of high essential oil and high herbage yield. These 14 lines were planted in RCBD design along with the check variety with three replications. Significant differences were observed in most of the agronomic characters and oil quality parameters among all mutant progenies. Among all the mutant lines, line no. 9 was found to be superior with plant height, herbage yield per plant, essential oil percent and monopodia length in comparison with the check variety. The multi-location trials revealed that the average fresh herbage yield (960 g/plant), oil content (3.10 %), and patchouli alcohol content (37.94 %) were also found to be significantly higher when compared to the check variety.